The clinical method as a learning content in the medicine career. - Luis Alberto Corona Martínez (Medisur)
The clinical method constitutes an important content in the learning process of the medical career. This article is aimed at reviewing the most essential aspects related to the topic in order to contribute to the deepening on this knowledge among professors students and professionals . It also offers information about the theoretical support given by outstanding Cuban professors on this topic which allowed the identification of a group of regularities that made the clinical method be a learning content with the category of invariant of knowledge, so it is indispensable to continue its teaching and to stimulate its use in practice.